Correction: Fluorescent vesicles formed by simple surfactants induced by oppositely-charged carbon quantum dots. Issue 87 (14th October 2016) - Sun, Xiaofeng; Zhang, Qinghong; Yin, Keyang; Zhou, Shengju; Li, Hongguang
Abstract : Correction for 'Fluorescent vesicles formed by simple surfactants induced by oppositely-charged carbon quantum dots' by Xiaofeng Sun et al., Chem. Commun., 2016, 52, 12024–12027.